Relations between main QED and background processes at interaction of the photons with the target of the photon polarimeter - Burdeinyi, D.D.; Ganenko, V.B.; Peresun’ko, Y.P.; Shapoval, I.M.; Vashchenko, G.A. (Вопросы атомной науки и техники, 2007)
The simulation of the processes which take place at the photon interaction with matter of the polarimeter target has been carried. The relations between main QED and background processes were studied. It was found that d-electron production is the basic background process for polarimeter based on the triplet photoproduction reaction. Their total contribution is no less ~ 20 - 30% even for optimal polarimeter target (plastic with 0.1 - 0.3mm thickness).